Management of Leadership Roles among Third Line Managers of Educational Institutes - Negi, Naveen (International Journal of Psychosocial Rehabilitation, 2019)
Leaders in today’s "flat" organisations have more autonomy than in the past. Leadership is about inspiring others to work together towards a common goal, whereas authority is about getting others to do what you want them to do without question or fear of repercussions. Because it appeals to the intellect and logical behaviour rather than the potent existential forces at the core of motivation, authority is unable to create the conviction or emotional devotion that leadership generates. The most effective corporate executives are aware of this fact and are thus gentle when delegating authority. They serve as role models for actions that build trust and responsibility, and they make use of informal networks and channels to motivate others throughout the organisation to make a difference.